THE INFLUENCE OF PRODUCT QUALITY, BRAND IMAGE, AND BRAND AMBASSADOR ON MS GLOW PURCHASE DECISIONS IN BATURITI, TABANAN REGENCY, BALI PROVINCE - Ni Ketut Oni Widarianti; Ni Made Ary Widiastini; Putu Indah Rahmawati (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2026)
This study aims to describe and examine the influence of several variables, namely: (1) product quality, (2) brand image, (3) brand ambassador, and (4) product quality, brand image, and brand ambassador simultaneously on the purchasing decisions of MS Glow products in Baturiti, Tabanan Regency, Bali Province. The population of this study consists of all MS Glow consumers in the Baturiti area. The sample was determined using purposive sampling, with the criteria that respondents must have made at least two purchases, resulting in a total of 180 respondents. This study is designed as causal quantitative research. Data were collected using a questionnaire instrument containing statements related to product quality, brand image, brand ambassador, and purchase decisions. The data were analyzed using simple linear regression and multiple linear regression to determine the partial and simultaneous effects between variables. The results show that: (1) product quality has a positive and significant effect on purchase decisions; (2) brand image has a positive and significant effect on purchase decisions; (3) brand ambassador has a positive and significant effect on purchase decisions; and (4) product quality, brand image, and brand ambassador simultaneously have a positive and significant effect on purchase decisions of MS Glow products in Baturiti. Therefore, improving product quality, strengthening brand image, and selecting the right brand ambassador can serve as effective strategies to enhance the purchasing decisions of MS Glow consumers in Baturiti.